Investigating links between Trichomonas vaginalis, T. vaginalis virus, Mycoplasma hominis, and metronidazole resistance - Govender, Rowen; Mabaso, Nonkululeko; Abbai, Nathlee S (The Journal of Infection in Developing Countries, 2024)
Introduction: Trichomonas vaginalis (TV) is the etiological agent of the common non-viral sexually transmitted infection (STI), trichomoniasis. TV can inherently harbour Mycoplasma hominis and Trichomonas vaginalis virus (TVV) species. Endosymbiosis of TV with M. hominis and TVV may contribute to metronidazole resistance in this pathogen. This study determined the prevalence of TVVs across clinical isolates of TV, as well as the symbiosis between TV, TVV, and M. hominis in relation to metronidazole resistance. Methodology: Twenty-one clinical isolates of TV were analysed in this study. The isolates were subjected to drug susceptibility assays using varying concentrations of metronidazole. Nucleic acids (RNA and DNA) were extracted from the isolates for molecular assays. The presence of intracellular M. hominis was determined by 16S rRNA polymerase chain reaction (PCR) with specific primers. The presence of the individual TVVs was determined by PCR using gene specific primers with template cDNA. Results: The prevalence of TVV and M. hominis were 76% (16/21) and 86% (18/21), respectively. No significant associations were observed between the presence of TVV and clinical symptoms. A significant association was noted between the coinfection of TVV4 and M. hominis (p = 0.014). The presence of any TVV was significantly associated with metronidazole susceptibility patterns (p = 0.012). No significant associations were noted between the coinfection of endosymbionts and metronidazole resistance. Conclusions: The information obtained displays the ability of TV to form an endosymbiotic relationship with several microorganisms, simultaneously. Based on these findings, both endosymbionts pose no significant influence on metronidazole resistance.